The Boundaryless Career Attitude and Organisational Commitment among Public Accountants in Penang, Malaysia - Wei, Gim Chien (Journal of Social and Development Sciences, 2012)
This paper aims to study the impact of boundaryless career attitude (organisational mobility preference and boundaryless mindset) on organisational commitment (affective commitment, continuance commitment, and normative commitment). Specifically, we predicted that employees who demonstrate a high boundaryless career attitude would be less committed to their employers. A sample of 132 public accountants was drawn from 15 accounting firms in Penang. A three-stage sampling was used in this study started with cluster sampling, followed by systematic sampling, and finally convenience sampling. Multiple regression analysis was used in the study and the results shown that organisational mobility preference was significantly negatively related to affective commitment, continuance commitment, and normative commitment. It also revealed that boundaryless mindset was significantly negatively related only to continuance commitment. Theoretically, the findings mainly supported the findings by Briscoe and Finkelstein (2009). Practically, the findings implied that practitioners of accounting firms should implement policies to cater to the needs of the boundaryless career actors by providing career relevant skills, training, meaningful jobs, and opportunities for secondment. In conclusion, this research revealed the growing importance of the boundaryless career attitude in affecting organisational commitment among public accountants in Penang, Malaysia.